Renaissance der Atomkraft? Vermutlich nicht! - Mez, Lutz; Schneider, Mycle (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2009)
The international nuclear lobby is constantly talking about a nuclear renaissance. But nuclear power is rather in the dusk than in the dawn. Missing industrial capacities, skyrocketing costs for raw materials and new nuclear power plants, the dramatic skilled worker/manager shortage and a sceptical financial sector are the main problems of nuclear industry. And nuclear technology as saviour against global warming is no good either.